2021
DOI: 10.1002/sd.2265
|View full text |Cite
|
Sign up to set email alerts
|

Toward achieving sustainable development: Searching for economic development and globalization thresholds in the foreign direct investment‐environmental degradation nexus

Abstract: The need to reduce environmental degradation has led to the identification of several factors influencing environmental degradation, with the inflows of foreign direct investments (FDI) touted as a key factor. However, findings produced from the existing studies on FDI-environmental degradation nexus are far from being conclusive, leaving policymakers under quandary regarding the precise effect of FDI on environmental degradation. We contribute to the FDI-environmental degradation nexus debate by examining how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…(2020) and Aluko et al (2021). However, this insignificant nexus may be explained by the offset mechanism as discussed by Koseoglu et al (2022): The urbanized locations with high population density have higher production and income, which may scale up CCEpc by stimulating the consumption of energy and emission-intensive products.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2020) and Aluko et al (2021). However, this insignificant nexus may be explained by the offset mechanism as discussed by Koseoglu et al (2022): The urbanized locations with high population density have higher production and income, which may scale up CCEpc by stimulating the consumption of energy and emission-intensive products.…”
Section: Resultsmentioning
confidence: 99%
“…Again, the AMG estimations of Doğan et al (2021) showed a positive association between population and carbon emissions for a panel of 28 OECD countries covering the 1990–2014 period. However, using the fixed effect panel threshold estimations in the case of 27 industrialized countries (including most European countries) over the 1991–2016 period, Aluko et al (2021) found that both population and urbanization had a negative association with the ecological footprint. Besides, the results of Koseoglu et al (2022) showed that urbanization did not have a statistically significant effect on the ecological footprint for the panel of top 20 green innovator countries (including 13 European countries) over the 1993–2016 period.…”
Section: Literature Development and Research Gapmentioning
confidence: 99%
See 1 more Smart Citation
“…Muhammad and Long (2021) show that pollution halo is the case for high income economies. The panel xed effects threshold estimation results by Aluko et al (2021) show that the level of income and globalization provide thresholds for the effect of FDI on pollution. They nd that FDI lowers pollution in economies with lower levels of income and globalization while it leads to environmental degradation in higher levels of income and more globalized countries.…”
Section: A Brief Literature Reviewmentioning
confidence: 98%
“…The FDI helps the nations fortify the cash flows in the economy while decreasing import/export imbalances (Zaman et al, 2021). In particular, FDI elevates economic development and the country's cash flows below the thresholds (Aluko et al, 2022). Therefore, the economist should pay attention to the impact of ICT on FDI to achieve sustainable economic growth.…”
Section: Study Backgroundmentioning
confidence: 99%